A Critical Evaluation of the Relationship Between the Effective Cation Exchange Capacity and Soil Organic Carbon Content in Swiss Forest Soils - Solly, Emily F.; Weber, Valentino; Zimmermann, Stephan; Walthert, Lorenz; Hagedorn, Frank; Schmidt, Michael W. I. (Frontiers in Forests and Global Change, 2020)
An improved identification of the environmental variables that can be used to predict the content of soil organic carbon (SOC) stored belowground is required to reduce uncertainties in estimating the response of the largest terrestrial carbon reservoir to environmental change. Recent studies indicate that some metal cations can have an active role in the stabilization of SOC, primarily by coordinating the interaction between soil minerals and organic matter through cation bridging and by creating complexes with organic molecules when their hydration shells are displaced. The effective cation exchange capacity (CEC eff.) is a measure that integrates information about available soil surfaces to which metal cations are retained. Therefore, we critically tested the relationship between CEC eff. and SOC content using regression analyses for more than 1000 forest sites across Switzerland, spanning a unique gradient of mean annual precipitation (640-2500 mm), elevation (277-2207 m a.s.l), pH (2.8-8.1) and covering different geologies and vegetation types. Within these sites, SOC content is significantly related to CEC eff., in both topsoils and subsoils. Our results demonstrate that in Swiss forest topsoils (<30 cm depth) there is a strong confounding effect of soil organic matter contributing between 35 % and 50 % to the total CEC eff. In subsoils, soil organic matter has a negligible contribution to CEC eff., and the variation of CEC eff. is associated to the presence of inorganic surfaces such as clay content as well as iron- and aluminum- oxides and hydroxides. At pH >5.5, between 59 and 83 % of subsoil CEC eff. originates from exchangeable calcium, whereas in acidic soils exchangeable aluminum contributes between 21 and 44 % of the CEC eff. Exchangeable iron contributes to less than 1 % of the variability in CEC eff. Overall this study indicates that in Swiss forests subsoils, CEC eff. strongly reflects the surface of soil minerals to which SOC can be bound by metal cations. The strength of the relationship between CEC eff. and SOC content depends on the pH of the soil, with the highest amount of variation of SOC content explained by CEC eff. in subsoils with pH >5.5.